Conceptualizing the ICEBERG problem-solving tool (IPST): A case study of an authorized automobile dealer in Riyadh, Saudi Arabia - Al-Homery, Hussein A.; Ashari, Hasbullah; Ahmad, Asmala (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
This study offers the practical part of our academic, conceptual paper on the ICEBERG Problem Solving Tool (IPST) within the application of a case study for an authorized automobile dealer in Riyadh, Saudi Arabia. The research is designed to represent how to operationalize the ICEBERG model practically in business problem-solving by using the concept of the IPST. The research is a qualitative case study within action research. It is a three cycles of action research. The tool application identified five levels of analysis besides the cross-functional analysis, the root cause of the persistent operational events and clearly showed the leverage points in the whole sales retail system. The “IPST” five levels of analysis enable us to see the complete picture of the cause of the events, touching the leverage points for decision-makers or the organizers. It is a quick fix for pining issues of repeated business events for the dealer's high performance. With theoretical roots in system thinking, this paper contributes to applying the ICEBERG model through “IPST” as a practical problem-solving tool for the business complex environment, has puzzles (operational killing events) around the whole business process and needs to be solved for a better performance.